TIM‐3 and CEACAM1 do not interact in cis and in trans - De Sousa Linhares, Annika (John Wiley and Sons Inc., 2020)

(untitled) (Eur J Immunol)
TIM‐3 has been considered as a target in cancer immunotherapy. In T cells, inhibitory as well as activating functions have been ascribed to this molecule. Its role may therefore depend on the state of T cells and on the presence of interaction partners capable to perform functional pairing. Carcinoembryonic antigen‐related cell adhesion molecule (CEACAM1) has been proposed to bind TIM‐3 and to regulate its function. Using a T cell reporter platform we confirmed CEACAM1‐mediated inhibition, but CEACAM1 did not functionally engage TIM‐3. TIM‐3 and CEACAM1 coexpression was limited to a small subset of activated T cells. Moreover, results obtained in extensive binding studies were not in support of an interaction between TIM‐3 and CEACAM1. Cytoplasmic sequences derived from TIM‐3 induced inhibitory signaling in our human T cell reporter system. Our results indicate that TIM‐3 functions are independent of CEACAM1 and that this receptor has the capability to promote inhibitory signaling pathways in human T cells.